Development of Sonar Sensor System for Autonomous Underwater Vehicles Application - Mohd Aras, Mohd Shahrieel; Hairi, Mohd Hendra; Kasdirin, Hyreil Anuar (2010)
This project is about the development of the sonar sensor system in purpose for Autonomous Underwater Vehicles (AUV) application. The concept of this project is using the ultrasonic sensor as a main device to transmit and receive the signal from the obstacle. The ultrasonic sensor will be combined to the ultrasonic circuit. Usually, the ultrasonic sensor is often used in robots for obstacle avoidance, map building and especially in navigation. Ultrasonic range sensor is works by emitting a short burst of 40 kHz sound. In addition, a small amount of sound energy is reflected by objects in front the device and returned to the detector or the receiver. The receiver sends this reflected signal known as echoes to the microcontroller to determine how far away the objects. However, to know how far away the objects it is using the speed of sound and time it took for the signal to be reflected. Unfortunately, echoes are not completely a product of distance. Different the medium will give the different speed and different result. It uses a Proowave Ultrasonic TXR and MikroC software as a compiler.